State-business relations as drivers of economic performance - Alberto Lemma; Dirk Willem te Velde (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Effective state-business relations (SBRs) have been lacking in industrial policy thinking despite the strong theoretical case for SBRs. The empirical study of state-business relations in developing countries has emerged only recently, with notable contributions starting in the mid-1990s, developing further in the 2000s and gaining more general acceptance in the 2010s. The evidence suggests that effective SBRs can matter for economic performance. The case studies suggest that SBRs can be effective (Mauritius) but also ineffective (Malawi). The quantitative evidence further suggests that high scores on SBRs measures are related to higher economic growth and firm level productivity.
Keywords: 330; state-business relations; industrial policy; growth